Policy and State in Complexity Economics - Wolfram Elsner (Routledge, 2017)
Complexity economics has developed into a powerful empirical, theoretical, and computational research program in the last three decades, advancing more realistic economics. It converges with long-standing heterodox schools, and its theoretical and empirical findings are consistent with older heterodox research interests and predictions. Economic complexity is characterized by path-dependence, idiosyncrasies, some self-organization capacity, structural emergence, and certain statistical distributions in economic topologies and motions, as complex economic systems move between building order and phases of sudden disorder. In agent-based systems, underlying “intentionality” of agents includes improving their performance, reducing perceived complexity, and generating social institutions. Boosted by the financial crisis 2008ff., a surge to explore complexity-economics' policy implications has emerged. This chapter will briefly review the literature on economic Complex Adaptive Systems (CAS) and derive implications for economic-policy interventions and the state to act upon socio-economic complexity. From an “evolution-of-cooperation” perspective, we exemplarily derive some more specific policy orientations, specified “framework-policy” or “interactive-policy” approaches, embedded in a conception that we call “new meritorics”. We consider some required structures and capacities that a modern effective state, capable of a strong and persistent, but learning and adapting “complexity policy”, should have.
Additional information: Submission to the Handbook of Government Intervention, ed. by Nikolaos Karagiannis and John E. King, forthcoming 2017.
Keywords: 330; Complex adaptive systems (CAS); complexity; economic policy; emergence; evolution; institutions; networks; self-organization; group size; state structure; qualification